2012
DOI: 10.1186/2045-3701-2-28
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of the wnt signaling pathway and TCF7L2 in diabetes mellitus: The current understanding, dispute, and perspective

Abstract: The Wnt signaling pathway was initially discovered for its role in tumorigenesis and the development of Drosophila and other eukaryotic organisms. The key effector of this pathway, the bipartite transcription factor β-cat/TCF, is formed by free β-catenin (β-cat) and a TCF protein, including TCF7L2. Extensive recent investigations have highlighted the role of the Wnt signaling pathway in metabolic homeostasis and its implication in diabetes and other metabolic diseases. Genome-wide association studies have show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
82
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 101 publications
3
82
0
8
Order By: Relevance
“…(3) showing that TCF7L2 variants were strongly associated with T2DM risk, several other studies consistently replicated this association in different ethnicities [reviewed in (4)]. Among the TCF7L2 variants, the rs7903146 (C/T) SNP seems to have the more robust effect in Caucasian populations (4,9). Here, we successfully replicated the association between the TCF7L2 rs7903146 SNP and risk for T2DM in Caucasian-Brazilian subjects from Southern of Brazil, probably under an additive inheritance model given that the risk conferred by the T/T genotype was higher than that conferred by heterozygous genotype.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…(3) showing that TCF7L2 variants were strongly associated with T2DM risk, several other studies consistently replicated this association in different ethnicities [reviewed in (4)]. Among the TCF7L2 variants, the rs7903146 (C/T) SNP seems to have the more robust effect in Caucasian populations (4,9). Here, we successfully replicated the association between the TCF7L2 rs7903146 SNP and risk for T2DM in Caucasian-Brazilian subjects from Southern of Brazil, probably under an additive inheritance model given that the risk conferred by the T/T genotype was higher than that conferred by heterozygous genotype.…”
Section: Discussionmentioning
confidence: 92%
“…Up to now, all of these studies firmly establish TCF7L2 gene as the strongest genetic risk factor for T2DM (4)(5)(6)(7)(8). Amongst the TCF7L2 variants, two intronic SNPs (rs12255372 and rs7903146) are the most closely associated with T2DM, and although both have showed a significant linkage disequilibrium (LD), the rs7903146 (C/T) variant seems to have the strongest effect in Caucasian populations (4,9).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…10 In exploring mechanisms underlying GLP-1 function, a few recent studies have demonstrated that the Wnt signaling pathway effector cat/TCF, a complex formed by free β-catenin (β-cat) and a member of the T-cell factor (TCF) family, regulates not only gut gcg mRNA transcription and GLP-1 production, but also GLP-1 function in pancreatic β-cells and brain neuronal cells. [11][12][13] Here we present our current knowledge on GLP-1 and its "degradation" products, and summarize our current understanding on the metabolic, proliferative and protective effects of GLP-1. We mainly focus on GLP-1 Downloaded by [Stony Brook University] at 06: 46 29 June 2015 termed as glucose competence.…”
Section: Introductionmentioning
confidence: 99%
“…The TCF7L2 gene is located on chromosome 10q25.3 and has been identified as a major T2DM susceptibility gene by a large scale genome-wide association study (GWAS) in 2006 (Grant et al, 2006). This important finding has been subsequently validated by genetic analyses of disease susceptibility in various ethnic groups in recent years (Ip et al, 2012).…”
Section: Introductionmentioning
confidence: 99%